Hubungan Dukungan Sosial dengan Tingkat Stres Narapidana Perempuan di Lapas Perempuan Kelas IIA Palembang - Jihan Fariza; Minarsi Minarsi (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
The number of inmates in Indonesia has continued to increase annually, resulting in overcrowding conditions in correctional institutions where inmate populations exceed facility capacity. This situation poses significant psychological challenges for inmates, particularly female inmates who are vulnerable to stress due to social isolation and limited access to support systems. This study aimed to examine the profile of social support, stress levels, and the relationship between social support and stress among female inmates at the Women’s Correctional Institution Class IIA Palembang. Social support in this study was not limited to family support but also included support from fellow inmates and correctional staff. A quantitative approach with a correlational design was employed. Data were analyzed using Spearman Rank Correlation with the assistance of SPSS version 26.0 for Windows. The results indicated that the majority of female inmates experienced moderate levels of social support (57 respondents; 71.25%) and moderate levels of stress (42 respondents; 52.25%). The correlation analysis revealed a negative correlation between social support and stress levels, with a correlation coefficient of r = âˆ’0.301 and a significance value (two-tailed) of p = 0.007 (p < 0.05). These findings indicate a low but statistically significant relationship between social support and stress levels among female inmates. Higher levels of social support were associated with lower stress levels, whereas lower social support was linked to higher stress levels. This study highlights the importance of strengthening social support systems within correctional institutions as a strategy to reduce stress among female inmates. The findings also provide practical implications for guidance and counseling services in correctional settings, emphasizing the role of psychosocial support from family, peers, and institutional staff in promoting inmates’ psychological well-being.